2020
DOI: 10.1080/14756366.2020.1774573
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and anticonvulsant effects evaluation of nonimidazole histamine H3receptor antagonists/inverse agonists containing triazole moiety

Abstract: Histamine H 3 receptors (H 3 R) antagonists/inverse agonists are becoming a promising therapeutic approach for epilepsy. In this article, novel nonimidazole H 3 R antagonists/inverse agonists have been designed and synthesised via hybriding the H 3 R pharmacophore (aliphatic amine with propyloxy chain) with the 1,2,4-triazole moiety as anticonvulsant drugs. The majority of antagonists/inverse agon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…The reduction or abolition of the THLE of mice was considered protective against the MES‐induced seizures. [ 23,29,48 ] Test compounds and positive drugs VPA (300 mg/kg) and PIT (10 mg/kg) were intraperitoneally administrated half an hour before the electric stimulation. To investigate the mechanism of action, the most promising compound, 5g , was chosen for a further test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction or abolition of the THLE of mice was considered protective against the MES‐induced seizures. [ 23,29,48 ] Test compounds and positive drugs VPA (300 mg/kg) and PIT (10 mg/kg) were intraperitoneally administrated half an hour before the electric stimulation. To investigate the mechanism of action, the most promising compound, 5g , was chosen for a further test.…”
Section: Methodsmentioning
confidence: 99%
“…Majority of them exhibited moderate‐to‐strong H 3 R inhibitory activities and exhibited antiseizure activity in an animal model of seizure. [ 29 ] JNJ‐6379490 is one of nonimidazole H 3 R antagonists containing an imidazo‐pyrimidine moiety. This compound possesses high potency (p K i = 8.6) as a neutral H 3 R antagonist with good brain penetration (rat: ED 50 = 0.2 mg/kg ip).…”
Section: Introductionmentioning
confidence: 99%
“…It was identified by using the intramolecular H 3 R biosensor based on bioluminescence resonance energy transfer (BRET) that is sensitive to the conformational dynamics of H 3 R and can be used to screen for the receptor agonists and inverse agonists in a live cell [ 133 ]. Nonimidazole antagonists/inverse agonists of H 3 R with nanomolar activity as anticonvulsant drugs were obtained by Song et al [ 134 ] by linking the H 3 R pharmacophore (aliphatic amine with propyloxy chain) with the 1,2,4-triazole moiety. Docking studies indicated that these ligands were bound to Y 3.33 and E 5.46 , and additionally to R 6.58 , F193 ECL2 and M 6.55 [ 134 ].…”
Section: Hr-targeted Ligands and Receptor Binding Site Of Inactivementioning
confidence: 99%
“…Nonimidazole antagonists/inverse agonists of H 3 R with nanomolar activity as anticonvulsant drugs were obtained by Song et al [ 134 ] by linking the H 3 R pharmacophore (aliphatic amine with propyloxy chain) with the 1,2,4-triazole moiety. Docking studies indicated that these ligands were bound to Y 3.33 and E 5.46 , and additionally to R 6.58 , F193 ECL2 and M 6.55 [ 134 ].…”
Section: Hr-targeted Ligands and Receptor Binding Site Of Inactivementioning
confidence: 99%
“…In 2020, novel nonimidazole H 3 R antagonists/inverse agonists, compound 14 in ▶Fig. 4, have been designed and synthesized by Song et al [34]. via hybriding the H 3 R pharmacophore (aliphatic amine with propyloxy chain) with the 1,2,4-triazole moiety as an-ticonvulsant drugs.…”
Section: Triazolementioning
confidence: 99%